Global Metal Music and Culture Current Directions in Metal Studies - Brown, Andy R.; Spracklen, Karl; Kahn-Harris, Keith; Scott, Niall (Routledge Studies in Popular Music, 2016)
This book defines the key ideas, scholarly debates, and research activities that have contributed to the formation of the international and interdisciplinary field of Metal Studies. Drawing on insights from a wide range of disciplines including popular music, cultural studies, sociology, anthropology, philosophy, and ethics, this volume offers new and innovative research on metal musicology, global/local scenes studies, fandom, gender and metal identity, metal media, and commerce. Offering a wide-ranging focus on bands, scenes, periods, and sounds, contributors explore topics such as the riff-based song writing of classic heavy metal bands and their modern equivalents, and the musical-aesthetics of Grindcore, Doom metal, Death metal, and Progressive metal. They interrogate production technologies, sound engineering, album artwork and band promotion, logos and merchandising, t-shirt and jewellery design, and fan communities that define the global metal music economy and subcultural scene. The volume explores how the new academic discipline of metal studies was formed, also looking forward to the future of metal music and its relationship to metal scholarship and fandom. With an international range of contributors, this volume will appeal to scholars of popular music, cultural studies, and sociology, as well as those interested in metal communities around the world.